Status of the Scholarship of Teaching and Learning in South African Universities - Pitso, Teboho (South African Journal of Higher Education, 2016)
The Scholarship of Teaching and Learning (SoTL) has become a global reality and most universities use it to achieve different objectives which indicate variation in how it is understood, used and encouraged. Some universities view it as the tool for broadening scholarship and thus as additional to established scholarships of discovery, integration and application similar to Boyer’s (1990) meaning. Other universities employ the SoTL in promotion and tenure while others have not engaged it in meaningful ways. This article provides the findings of the year-long study that focused on examining the constitution of the SoTL in seven South Africa universities in terms of how it was understood, used and encouraged. Written, oral and episodic accounts were elicited and analysed to illuminate current SoTL standing, value and transformative potential on teaching and learning. Current SoTL conceptions illuminate a researcher-centred SoTL and its impact on teaching and learning practices occupy the backseat.